2022
DOI: 10.3390/cimb44020053
|View full text |Cite
|
Sign up to set email alerts
|

ICOS Gene Polymorphisms (IVS1 + 173 T/C and c. 1624 C/T) in Primary Sjögren’s Syndrome Patients: Analysis of ICOS Expression

Abstract: Background: Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disease, which affects exocrine glands. T cell activation is a trigger mechanism in the immune response. Hyperreactivity of T cells and antibody production are features in pSS. ICOS can be critical in the pathogenesis of pSS. Methods: A total of 134 pSS patients and 134 control subjects (CS) were included. Genotyping was performed by PCR-RFLP. ICOS mRNA expression was quantified by real-time PCR, and CD4+ ICOS+ T cells were determined by flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
(67 reference statements)
1
4
1
Order By: Relevance
“…In the gene expression study, we showed a decrease in ICOS mRNA expression in SLE patients compared to HC. Our results do not corroborate with a recent study, which showed that ICOS mRNA expression levels are high in pSS patients compared to controls (García‐Espinoza et al., 2022). The low expression in our patients is probably related to the therapeutic effects of corticosteroids.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the gene expression study, we showed a decrease in ICOS mRNA expression in SLE patients compared to HC. Our results do not corroborate with a recent study, which showed that ICOS mRNA expression levels are high in pSS patients compared to controls (García‐Espinoza et al., 2022). The low expression in our patients is probably related to the therapeutic effects of corticosteroids.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in agreement with the study of García‐Espinoza et al. (2022), who found a CC genotype frequency of 1% for the rs10932029 polymorphism in the western Mexican population. In addition, Haimila et al.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…enhanced expression of icoS-expressing cd3+ T cells may suggest that the systemic lupus erythematosus (SLE) patients are at a more severe inflammatory status (22). Previous studies have reported increased icoS protein and mrna expression levels in the peripheral blood of patients Expression of ICOS in the salivary glands of patients with primary Sjogren's syndrome and its molecular mechanism with pSS (23,24). The present study found that the expression of icoS was shown to affect saliva weight and aquaporin 5 (AQP5) expression; however, the specific downstream signal transduction constituents involved remain unknown.…”
Section: Introductionmentioning
confidence: 99%